2022
DOI: 10.1186/s12891-022-05592-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between total bilirubin and bone mineral density level in adolescents

Abstract: Background Increasing bone mass accumulation in adolescence and obtaining greater peak bone mass is one of the effective methods to prevent osteoporosis in the future. We aimed to examine the association between total bilirubin and bone mineral density (BMD) level in adolescents. Methods We used the data from 2005–2010 and 2013–2014 cycles of National Health and Nutrition Examination Survey (NHANES). The BMD levels in the region of lumbar spine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Both studies excluded the effect of liver disease, but both had limited sample sizes and were restricted to the Korean population [15,16]. Another cross-sectional study based on the NHANES database indicated that TB was positively associated with BMD in the US adolescent population [17]. However, there are obvious methodological flaws in this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Both studies excluded the effect of liver disease, but both had limited sample sizes and were restricted to the Korean population [15,16]. Another cross-sectional study based on the NHANES database indicated that TB was positively associated with BMD in the US adolescent population [17]. However, there are obvious methodological flaws in this study.…”
Section: Discussionmentioning
confidence: 91%
“…There are currently 3 published retrospective observational studies on the association of TB with BMD [15][16][17]. Two retrospective studies from South Korea showed that TB was positively associated with BMD in middle-aged men and postmenopausal women; in other words, TB appears to act as a protective factor to reduce the risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxidative stress is generated when the antioxidant system is overwhelmed by these oxidants, leading to the pathogenesis of various diseases, including osteoporosis [ 36 ]. The circulating level of endogenous antioxidants, such as uric acid and bilirubin, has been associated with bone mineral density (BMD) in large epidemiological studies [ 37 , 38 ]. Similarly, dietary or circulating antioxidant levels, for example, vitamin E and vitamin C, have been linked positively with BMD in human studies [ 39 , 40 ].…”
Section: Pathophysiology Of Osteoporosismentioning
confidence: 99%